Revisiting the Self: Researching Minorities in Turkey - Karaosmanoglu, Kerem (SETA FOUNDATION, 2008)
Minorities have always been the subject of academic, journalistic and popular research in Turkey. The general trend of most of these analyses is to conceive of minorities as part of a wider international political structure, he it the international system, imperialism or an anti-national conspiracy against ethnic Turks. Within such pictures, a member of a minority group can hardly be recognized as an individual self with a sense of subjectivity. Thus, what is missing in most minority research in Turkey is an analysis of the self. This article argues that cultural studies can provide resources and inspiration for a new research paradigm for the study of minorities in Turkey through its use of qualitative anthropological methods such as participant observation, indepth interviews and focus groups. Only then can the minority self have a chance to say something of his/her own, breaking the shield of silence and the stigma of conspiracy discourse.
Keywords: Government & Law